Social life of free-living amoebae in aquatic environment— comprehensive insights into interactions of free-living amoebae with neighboring microorganisms - Fan, Shi; Shen, Yun; Qian, Li (Frontiers in Microbiology, 2024)
Free-living amoebae (FLA) are prevalent in nature and man-made environments, and they can survive in harsh conditions by forming cysts. Studies have discovered that some FLA species are able to show pathogenicity to human health, leading to severe infections of central nervous systems, eyes, etc. with an extremely low rate of recovery. Therefore, it is imperative to establish a surveillance framework for FLA in environmental habitats. While many studies investigated the risks of independent FLA, interactions between FLA and surrounding microorganisms determined microbial communities in ecosystems and further largely influenced public health.Here we systematically discussed the interactions between FLA and different types of microorganisms and corresponding influences on behaviors and health risks of FLA in the environment. Specifically, bacteria, viruses, and eukaryotes can interact with FLA and cause either enhanced or inhibited effects on FLA infectivity, along with microorganism community changes. Therefore, considering the co-existence of FLA and other microorganisms in the environment is of great importance for reducing environmental health risks.